Hyperhidrosis. Issue 7 (July 2017) - Webber, Lucy
Hyperhidrosis (HH) is a disorder involving the secretion of sweat in excess of that required for normal physiological thermoregulation. Most patients with HH experience some degree of functional and psychological dysfunction as a result of their condition. Despite this, a huge majority of patients do not recognise their excessive sweating as a medical condition. This article aims to cover the diagnosis, management and referral of patients with HH.